Efektivitas Adaptasi Teknologi pada Kinerja Sistem Surveilans Malaria di Era COVID-19 untuk Negara Berkembang: Sebuah Kajian Sistematis - Valerie Josephine Dirjayanto; Celina Azhura Harmen; Muhammad Athallah Arsyaf (Direktorat Penerbitan dan Publikasi Ilmiah, Universitas Surabaya, 2022)
Abstract—Due to the limitations of the current malaria surveillance system, the use of technology for diagnostics and treatment is an important factor in controlling the number of malaria cases at local and national levels. However, studies on the effectiveness of the implementation of technology-assisted surveillance systems have yet to be found. The literature search was conducted based on the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA). This systematic review was conducted using PubMed, Scopus, ScienceDirect, Cochrane, Google Scholar, and EBSCOHost databases. Assessment of study bias and methodology was carried out with the National Institutes of Health (NIH) Quality Assessment Tool for Observational Cohort and Cross-Sectional Studies. The literature search yielded 9 literatures with a total subject of 322,168. The usage of technology in malaria surveillance system has been shown to shorten the time of discovery, reporting, case follow-up response. The interventions also improve the completeness and accuracy of the data and improve user-supervisor coordination while also receiving positive responses from the users. This study demonstrates the effectiveness of implementing a technology-based malaria surveillance system in developing countries in the COVID-19 era. Further research with larger and uniform population is needed to strengthen the evidence for successful implementations. Keyword: malaria, surveillance, mobile health, low resource countries, covid-19 Abstrak—Mengingat keterbatasan sistem surveilans malaria yang ada saat ini, penggunaan teknologi dalam melakukan pelaporan diagnostik maupun pengobatan kasus merupakan faktor penting dalam menentukan pengendalian jumlah kasus malaria pada tingkat lokal dan nasional. Namun, kajian mengenai efektivitas penggunaanya masih belum dapat ditemukan. Pencarian literatur studi dilakukan berdasarkan the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA). Kajian sistematis ini dilakukan melalui database dan. Penilaian bias dan metodologi studi dilakukan dengan National Institutes of Health (NIH) Quality Assessment Tool for Observational Cohort and Cross-Sectional Studies. Pencarian literatur menghasilkan 9 literatur dengan total subjek 322.168 orang. Penggunaan teknologi dalam sistem surveilans malaria terbukti mempersingkat waktu penemuan, waktu pelaporan, hingga waktu respon follow-up kasus. Selain meningkatkan kelengkapan dan keakuratan data, teknologi tersebut juga membantu koordinasi pengguna dengan supervisor dan mendapatkan respon positif dari pengguna. Kajian sistematik ini menunjukkan efektivitas penerapan sistem surveilans malaria berbasis teknologi pada negara berkembang di era COVID-19. Penelitian lanjut dengan populasi yang besar dan seragam dibutuhkan untuk memperkuat bukti kesuksesan penerapan. Kata Kunci: malaria, surveilans, mobile health, negara sumber daya rendah, covid-19